Association between purchasing behaviors and cigar use: A longitudinal analysis of Waves 1-3 of the Population Assessment of Tobacco and Health (PATH) Study. - Jessica L King (PLoS ONE, 2020)
Introduction Over 120 US jurisdictions have implemented policies mandating minimum cigar pack quantities, yet little empirical research exists on the relationship between pack quantity and use. We examined whether cigar use was associated with purchasing cigars by the box/pack or as singles, purchase quantity, and price paid per cigar. Methods Data are from Waves 1-3 (2013-2016) of the Population Assessment of Tobacco and Health (PATH) Study, analyzed in 2019. The sample included adults who reported current use of any type of cigars (cigarillos [N = 3,051], traditional cigars [N = 2,586], and filtered cigars [N = 1,295], including with marijuana) at Wave 1. For each cigar type, a generalized estimating equation model was used to examine the population-averaged effects of purchasing behavior on cigar use. Results Cigar users of each type who purchased by the box or pack smoked more per day than users who purchased singles (cigarillos: β = 1.02, p<0.0001; traditional cigars: β = 1.40, p<0.0001; filtered cigars: β = 2.55, p<0.01). Cigar users who purchased larger quantities smoked more per day (cigarillos: β = 0.16, p<0.0001; traditional cigars: β = 0.04, p<0.0001; filtered cigars: β = 0.24, p<0.0001). Higher price per cigar was significantly associated with smoking fewer traditional cigars (β = -0.12, p<0.01) and filtered cigars (β = -0.86, p = 0.02), but not cigarillos (β = 0.08, p = 0.62). Conclusions Smaller pack quantities and higher price per cigar were associated with smoking fewer cigars per day. Given the authority of the Food and Drug Administration and local jurisdictions over cigar pack quantity, this study provides data pertinent to potential minimum and maximum package quantity regulations and policies.